Dirichlet summations and products over primes - Geoffrey B. Campbell (International Journal of Mathematics and Mathematical Sciences)
We derive new classes of infinite products taken over the primes, for example expressing ∏p(11−p−n)(1−p−m)−1 as an infinite produce of Riemann zeta functions, this product being taken over the set of rational numbers α/β geater than zero with a relatively prime to βζ(n)∏α,βζ(αm+βn)1/β.